Spectral Transmission of Sunglasses from Patients with Various Inherited Retinal Diseases. - Vezinaw, Chloe M. (Optometry & Visual Performance, 2020)
Background: Light comprised of ultraviolet and blue wavelengths is known to cause potential damage to the retina after chronic exposure. Those with already compromised retinas are potentially at a greater risk of experiencing damage from this light exposure. Subsequently, it is likely important that such patients wear the most optimal sun protection to try and diminish this potential risk. As such, we sought to determine the effectiveness of their sunglass lenses for filtering blue and ultraviolet wavelengths of light in a group of patients with compromised retinas. Methods: Forty subjects with various inherited retinal diseases were included in the study. We inquired by a simplified questionnaire how patients selected their most recent sunglasses and how satisfied they were for reducing their discomfort from light exposure. The light transmission quality of their selected lenses was measured with a spectral transmission lensometer. Results: The average percentage of blue light transmitted from subjects' measured lenses was 13.9% (range 0-60%) and that most (70.0%) subjects' lenses blocked all UVB and UVA light. Most (82.5%) subjects were either very satisfied or satisfied with the protection of their current sunglasses from discomfort during light exposure. Their sunglasses were mainly selected due to a recommendation by an eye care professional (35.0%) or by fashion (30.0%). Conclusion: Most subjects were satisfied with the comfort afforded by their sunglasses although, on the whole, they did not provide ideal protective qualities in reference to filtering blue light. Eye care providers and fashion made the most contributions towards sunglass selection.